Orphan nuclear receptor TR3/Nur77 improves wound healing by upregulating the expression of integrin β4. Issue 1 (17th October 2014) - Niu, Gengming; Ye, Taiyang; Qin, Liuliang; Bourbon, Pierre M.; Chang, Cheng; Zhao, Shengqiang; Li, Yan; Zhou, Lei; Cui, Pengfei; Rabinovitz, Issac; Mercurio, Arthur M.; Zhao, Dezheng; et al.
Abstract : Tissue repair/wound healing, in which angiogenesis plays an important role, is a critical step in many diseases including chronic wound, myocardial infarction, stroke, cancer, and inflammation. Recently, we were the first to report that orphan nuclear receptor TR3/Nur77 is a critical mediator of angiogenesis and its associated microvessel permeability. Tumor growth and angiogenesis induced by VEGF‐A, histamine, and serotonin are almost completely inhibited in Nur77 knockout mice. However, it is not known whether TR3/Nur77 plays any roles in wound healing. In these studies, skin wound‐healing assay was performed in 3 types of genetically modified mice having various Nur77 activities. We found that ectopic induction of Nur77 in endothelial cells of mice is sufficient to improve skin wound healing. Although skin wound healing in Nur77 knockout mice is comparable to the wild‐type control mice, the process is significantly delayed in the EC‐Nur77‐DN mice, in which a dominant negative Nur77 mutant is inducibly and specifically expressed in mouse endothelial cells. By a loss‐of‐function assay, we elucidate a novel feed‐forward signaling pathway, integrin β4 → PI3K → Akt → FAK, by which TR3 mediates HUVEC migration. Furthermore, TR3/Nur77 regulates the expression of integrin β4 by targeting its promoter activity. In conclusion, expression of TR3/Nur77 improves wound healing by targeting integrin β4. TR3/Nur77 is a potential candidate for proangiogenic therapy. The results further suggest that TR3/Nur77 is required for pathologic angiogenesis but not for developmental/physiologic angiogenesis and that Nur77 and its family members play a redundant role in normal skin wound healing.‐Niu, G., Ye, T., Qin, L., Bourbon, P. M., Chang, C., Zhao, S., Li, Y., Zhou, L., Cui, P., Rabinovitz, I., Mercurio, A. M., Zhao, D., Zeng, H. Orphan nuclear receptor TR3/Nur77 improves wound healing by upregulating the expression of integrin b4. FASEB J. 29, 131–140 (2015). www.fasebj.org